Analysis of Financial Literacy on Community Investment Decisions (Study in Tanjung Medan Village, Labuhanbatu Regency) - Mulkan Ritonga; Rahma Muti'ah (Garuda Prestasi Nusantara Consulting, 2023)
This study aims to analyze the impact of financial knowledge on individual investment decisions. The tests focus on each indicator to determine which factors most influence individual investment decisions. This study involved 80 respondents residing in Tanjung Medan Village and were identified using a non-probability sampling technique with a purposive sampling design. This study is descriptive and quantitative with primary data collected using questionnaire techniques. The results of the study show that financial literacy indicators, specifically general financial knowledge, lending and saving, investing and risk management, have a positive and significant impact on decision-making. investment decisions, both partially and simultaneously, in which loan and savings indices have the dominant influence. Meanwhile, in the determination coefficient test, financial knowledge has an 89.70% influence on people's investment decisions, the rest is affected by other factors not considered in the study.